2020
DOI: 10.3389/fpsyt.2020.00390
|View full text |Cite
|
Sign up to set email alerts
|

Using Administrative Data to Predict Suicide After Psychiatric Hospitalization in the Veterans Health Administration System

Abstract: There is a very high suicide rate in the year after psychiatric hospital discharge. Intensive postdischarge case management programs can address this problem but are not costeffective for all patients. This issue can be addressed by developing a risk model to predict which inpatients might need such a program. We developed such a model for the 391,018 short-term psychiatric hospital admissions of US veterans in Veterans Health Administration (VHA) hospitals 2010-2013. Records were linked with the National Deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 114 publications
2
38
0
Order By: Relevance
“…Our random forests’ operating characteristics are comparable with those of a previous study that used machine learning to predict postdischarge suicide among veterans, 10 which found that the 5% of patients with the highest predicted risk accounted for 32% of suicides in the 1 month after psychiatric hospital discharge. In our study, persons in the highest 5% of predicted suicide risk accounted for 23% of all suicide deaths among men and 38% among women 1 month postdischarge.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our random forests’ operating characteristics are comparable with those of a previous study that used machine learning to predict postdischarge suicide among veterans, 10 which found that the 5% of patients with the highest predicted risk accounted for 32% of suicides in the 1 month after psychiatric hospital discharge. In our study, persons in the highest 5% of predicted suicide risk accounted for 23% of all suicide deaths among men and 38% among women 1 month postdischarge.…”
Section: Discussionsupporting
confidence: 78%
“…This suggests that a prevention program delivered to only 5% of hospitalised patients with the highest predicted risk could capture a large proportion of patients who would otherwise die by suicide. 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total number of potential suicide risk factors examined was 12 242 (mean per model = 135, s. d. = 387) after excluding the samples that used clinical judgement (in which the number of potential and included suicide risk factors could not be ascertained) and a single machine-learning study that used 8071 predictor variables. 62 The total number of included suicide risk factors in the suicide prediction models could not be ascertained exactly because some machine-learning studies did not clarify this precisely, but there were at least 777 (mean per model 8.7, s.d. = 9.9) of which 598 could be identified and tabulated (Supplementary Material Table S1, available at https://doi.org/10.1192/bjo.2020.162).…”
Section: Searches and Data Extractionmentioning
confidence: 99%
“…In addition to the NLP-derived SBDH variables, we also identified social determinants from the structured data. We used the ICD-9 codes from patient diagnoses [ 33 ] to construct these 3 SBDH variables: (1) housing insecurity, (2) unemployment, and (3) social isolation. These were later integrated with the NLP-derived SBDH variables and prioritized in case of any mismatch.…”
Section: Methodsmentioning
confidence: 99%